Base-controlled 1, 6-enyne-bicyclization: divergent synthesis of benzo[b]fluorenones and benzo[b]fluorenols. Issue 17 (28th April 2016) - Hao, Wen-Juan; Zhou, Peng; Yang, Zheng; Jiang, Bo; Zhang, Jin-Peng; Tu, Shu-Jiang
Abstract: An interesting base-controlled protocol for the divergent and atom-economic synthesis of benzo[ b ]fluorenones and benzo[ b ]fluorenols with the great diversity in substitution patterns has been developed. Started from readily available 1, 6-enynes, good to excellent yields of the corresponding tetracyclic benzo[ b ]fluorenones and benzo[ b ]fluorenols can be chemoselectively achieved under metal-free conditions. Notably, only K2 CO3 or Et3 N was required as the promoter here and the reaction can work well in a high-selective manner. Graphical abstract: